Lewtonian space: Val Lewton's films and the new space of horror. Issue 2 (1st November 2010) - Telotte, J. P
During the 1940s the Val Lewton unit at RKO Studios produced a string of horror films that were highly lauded for their subtle approach to the genre, which represented a distinct break from earlier horror films that were characterized by their emphasis on monstrous figures and exaggerated, expressionist-influenced imagery. A significant element of that influence, however, has so far gone unexplored, particularly what we might term the space of horror. Drawing on architectural developments and theory in the late modernist period, particularly as articulated by Anthony Vidler, this article examines how the Lewton films drew on this new sense of space, a space that emphasized not structures or containment, but rather the emerging psychological and social dimensions of the era. Because of wartime restrictions and the economical practices of B-film production, the Lewton films (and as illustrations this article draws examples from each of the three directors who worked in this unit Jacques Tourneur, Mark Robson and Robert Wise) almost had to function in a different register than the earlier wave of horror films with their emphases on old dark houses and castles, on werewolves and vampires. The new spatial strategy that they evolved, however, not only accommodated those period and industrial limitations, but also opened up a new possibility for representing narratives of power and dread one that mobilized space as a placeholder for all of our psychic projections and fears.